Níveis de arginase, óxido nítrico e o efeito da pge2 na produção de tnf-α em linfonodo de cães com leishmaniose visceral - Venturin, Gabriela Lovizutto [UNESP] (2015)
Visceral leishmaniasis (VL) is a chronic disease that can be fatal to humans and dogs. The disease is caused by the intracellular parasite Leishmania infantum and is transmitted by the bite of the sandfly (phlebotomines). In dogs, VL is observed as an intense chronic inflammatory reaction in the liver, spleen, skin, bone marrow and lymph nodes. Arginase activity is important in VL because an increase of this enzyme may contribute to the multiplication of the parasite and a reduction of nitric oxide (NO) synthesis, predisposing a macrophage to infection. Prostaglandin E2 (PGE2) can play a regulatory role in the production of tumor necrosis factor (TNF-α) and interleukin-10 (IL-10), however, there have been no studies in dogs with LV. This study aimed to evaluate the arginase activity in adherent macrophages cultivated from the lymph nodes of 18 healthy and 23 naturally infected dogs and to examine levels of NO and PGE2 in the supernatant of these cultures. The regulatory effect of PGE2 on the production of TNF-α and IL-10 was also evaluated in supernatants of total lymph node leukocytes cultures. These results help to clarify the mechanisms of the immune response in CVL.